On the fuzzy multi-objective linear programming problem: Goal programming approach - Kuwano, Hiroaki (Fuzzy Sets and Systems, 1996)
For a fuzzy multi-objective linear programming problem, we propose a substitute problem. The problem is given as the minimization problem, the objective function of which is the distance between the l -ary restricted α-optimal values at each α-optimal solutions (Kuwano et al., 1994) and l -ary objective functions with fuzzy parameters.